THE RELATIONSHIP BETWEEN AWARENESS AND KNOWLEDGE LEVEL OF CLINICAL DENTAL STUDENTS ABOUT ORAL CANCER DISEASE - Stefani Marlene Tarius; Tira Hamdillah Skripsa; Diah Rahayu Wulandari (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Oral cancer is the sixth most common type of cancer with two out of three cases occurring in developing countries. As clinical dental students, knowledge and awareness about oral cancer should also be improved with the aim of helping them as future dentists to be more ready to act immediately in prevention phase and early diagnosis of oral cancer.Objective: This study aims to analyze the relationship between the level of knowledge and the level of awareness of dental students about oral cancer.Methods: An observational analytic study with a cross sectional study design. A total of 91 clinical dental students participated in this study. Oral cancer awareness and knowledge level were measured using a pre-validated questionnaire. Spearman’s rho correlation test was used to determine the association between oral cancer awareness and knowledge level of clinical dental students.Results: Out of 91 clinical dental students, 61 (67%) students got excellent-graded awareness and 57 (62,6%) students got good-graded knowledge. Spearman rho correlation test showed oral cancer awareness were significantly associated (p=0,007) with oral cancer knowledge level. Significant positive linear correlations (r=0,279) between oral cancer awareness and knowledge level were also observed from the study results.Conclusion: Clinical dental students’ oral cancer awareness and knowledge level are significantly associated.